Emission evaluation of a diesel engine generator operating with a proportion of isobutanol as a fuel additive in biodiesel blends. (5th May 2016) - Yang, Po-Ming; Lin, Kuang C.; Lin, Yuan-Chung; Jhang, Syu-Ruei; Chen, Shang-Cyuan
Highlights: Diesel/biodiesel/isobutanol blends significantly decrease PM and NOx emissions. Blends are shown to inhibit the formation of carbonyl compounds. The brake specific fuel consumption is increased with blends. Abstract: Isobutanol is one of the next-generation biofuels that may potentially help to relieve the energy crisis and environmental problems. This study investigates the emissions of carbonyl compounds and regulated pollutants that are produced from diesel engine combustion in idle mode. Varied mixtures of diesel, biodiesel (up to 40 vol.%), and isobutanol (10 vol.%) components are compared with premium diesel fuels in terms of their combustion emissions. Experimental results indicate that major carbonyls in the exhaust, in order, are formaldehyde, acetaldehyde, and acrolein, and they account for 77.7% to 83.8% of the total carbonyl compound concentrations emitted from a diesel engine fueled with all test fuels including diesel. With the increase of the biodiesel proportion in the blends of diesel–biodiesel–isobutanol, carbon monoxide (CO), nitrogen oxide (NOX ), and particulate matters (PMs) are decreased by an average of 3.45, 32.5, and 38.5 vol.%, respectively. The effect of the biodiesel proportion in the blends on carbonyl emissions is significant due to the fact that formaldehyde and acetaldehyde are able to be reduced by 14.4 to 54.5 vol.% in average, respectively. Although the blended fuels benefit pollutant emissions, an increase of brake specific fuel consumption is observed with an elevated percentage of biodiesel.